Practical network automation : leverage the power of Python and Ansible to optimize your network - Ratan, Abhishek (Packt Publishing, 2017)
Get More from your Network with Automation tools to increase its effectiveness. About This Book " Get started with network automation (and different automation tasks) with relevant use cases " Apply software design principles such as Continuous Integration and DevOps to your network toolkit " Guides you through some best practices in automation Who This Book Is For If you are a network engineer looking for an extensive guide to help you automate and manage your network efficiently, then this book is for you. What You Will Learn " Get the detailed analysis of Network automation " Trigger automations through available data factors " Improve data center robustness and security through specific access and data digging " Get an Access to APIs from Excel for dynamic reporting " Set up a communication with SSH-based devices using netmiko " Make full use of practical use cases and best practices to get accustomed with the various aspects of network automation In Detail Network automation is the use of IT controls to supervise and carry out every-day network management functions. It plays a key role in network virtualization technologies and network functions. The book starts by providing an introduction to network automation, SDN, and its applications, which include integrating DevOps tools to automate the network efficiently. It then guides you through different network automation tasks and covers various data digging and reporting methodologies such as IPv6 migration, DC relocations, and interface parsing, all the while retaining security and improving data center robustness. The book then moves on to the use of Python and the management of SSH keys for machine-to-machine (M2M) communication, all followed by practical use cases. The book also covers the importance of Ansible for network automation including best practices in automation, ways to test automated networks using different tools, and other important techniques. By the end of the book, you will be well acquainted with the various aspects of network automation. Style and approach A clear, concise, and straightforward book that will enable you to automate networks and improve performance